Student Tardiness in Vocational Schools: Causes, Consequences, and Management Strategies - Okhtafia, Eka Sinta; Ulum, Risma Anisa Zahrotul; Hanaya, Rizky Risa; Zamroni, Zamroni; Budianti, Eni; Probowati, Devy (Proceedings Series of Educational Studies, 2024)
This study aims to analyze the habitual tardiness behavior of vocational high school students. The research method used is a case study. Data collection techniques included observation, interviews, and documentation. The subjects of this study were five students who exhibited tardiness behavior over a one-month period. The research data consisted of descriptive narratives supported by field notes, including a summary book of tardiness and interviews with the subjects at the vocational school. Based on the data obtained, there are two main reasons for students' tardiness: waking up too late and being caught in traffic. This is supported by data analysis indicating that the level of tardiness among students at the vocational school is high. Despite being given several sanctions, students continue to be tardy. This habitual tardiness disrupts the teaching and learning process, which can significantly impact their academic performance. The recommendation based on these findings is the implementation of self-management techniques for students with habitual tardiness behavior. Keywords: habitual tardiness; vocational high school students